Calculation of beam structures under constrained torsion Methodological guidelines for solving problems from the discipline "Special Course of Metal Structures" and "Specialized Training Discipline in Metal Structures" - Bilyk, Serhiy Ivanovych; Skliarov, Ihor Oleksandrovych; Skliarova, Tetiana Serhiivna; Honcharuk, Oleksii Dmytrovych (КНУБА, 2025)
Theoretical information for determining the stress-strain state of beam structures under constrained torsion is provided. Additionally, examples of calculating certain types of beam structures are given, and expanded assortments of rolled metal products with the necessary sectoral geometric characteristics are presented. Intended for master’s degree applicants of specialty G19 "Construction and civil engineering". Надано теоретичну інформацію для визначення напружено-деформованого стану балкових конструкцій при вимушеному крученні. Додатково наведено приклади розрахунку певних типів балкових конструкцій та представлено розширені сортаменти металопрокату з необхідними секторальними геометричними характеристиками. Призначено для здобувачів другого (магістерського) рівня вищої освіти за спеціальністю G19 "Будівництво та цивільна інженерія".
Keywords: Beam Structures; Constrained Torsion; Rolled Metal Products